Examining the Impact of Cultural Norms on Mental Health Stigma in Pakistan: A Qualitative Approach - Sidra Mustaqeem ,; Uzma Rani,; Seher Eida,; Bushra Nagaria,; Kauser Akbar,; Saleha Qamer, (Dialogue Social Science Review (DSSR), 2025)
In this paper, the emphasis is made on such cultural norms of Pakistan as family honor, gender roles and mental illness misconceptions in relation to mental health stigma. Exploratory research design was applied; data collected by personal interviews of 50 people (25 male, 25 female) aged between 18 and 45 years from the urban and rural areas. They also pointed out that 86% of participants failed to seek care due to family honor as 43/50) and 68% of participants feared being stigmatized and socially isolated (34/50). The results demonstrated that there was a difference between the two sexes, of female participants 72% (18/25) reported higher stigma related with mental health than males 52% (13/25). Pre-study attitudes regarding mental illness were as follows: 58% (29/50) thought it to be a supernatural problem, and 76% (38/50) as a mark of weakness. The study, therefore, calls for culturally sensitive programs question these standards and enhance mental health literacy to remove stigma and encourage use of mental health services.